ANALISIS POLA KOMUNIKASI REMAJA PADA KELUARGA BROKEN HOME: Studi Deskriptif Kualitatif Pada Remaja Di Cakung Timur - Bunaya Putri Zulfikar, (2023)
Adolescence is a period of transition from childhood to adulthood, with an age range of 10-24 years characterized by physical and psychological changes. Adolescence, a period of upheaval, and various deviations that occur are committed by adolescents, one of the factors caused by ineffective communication with family. This study focuses on adolescent communication patterns in the familybroken home in the East Cakung area. The method used is descriptive qualitative with centralized interviews, with data collection through interviews and observation. The results showed that communication patterns after parents divorced, adolescent communication was more intimate after divorce with only one family member, until it reached a stable stage orstable sage. In conclusion, from the communication patterns of the four families that were the object of the study, it was found that adolescents had significant changes in communication before and after their parents divorced, both in terms of openness. trust, as well as adjustments to multiple roles, so that it appears that the pattern that stands out in broken home families is a two-way communication pattern, where adolescents are more comfortable voicing opinions or providing information to only one family member, rather than telling stories in front of all family members